(untitled) (Research, Society and Development, 2024)
The objective of the study is to understand the experiences of family members living with children with ASD. This is an narrative review of the literature, which used the Medical Literature Analysis and Retrievel System Online (MEDLINE) and Latin American and Caribbean Literature in Health Sciences (LILACS) as databases. Data were collected in November 2023 and the descriptors used were: Family AND Child AND Autism Spectrum Disorder. For the inclusion criteria, the following were used: primary articles, available in full and free of charge, published in the last five years, without language restrictions, that addressed the proposed theme. The results demonstrate that the emotional impact immediately after the diagnosis is significant, leading to intense emotions and adjustments to assimilate the news. Furthermore, a second critical moment was identified, occurring a few years after the diagnosis, characterized by the caregiver’s peak crisis, marked by feelings of overload and impotence. Adapting to the new routine, integrating new habits and reorganizing the lifestyle emerged as recurring challenges, especially for mothers, who often play a central role in caring for children with ASD. Furthermore, the difficulty of communication and interaction was identified as an additional aspect present in the families’ experiences, generating frustration and making it even more difficult to adapt to daily life with the child with ASD. It is concluded that family members face significant challenges when trying to accept and adapt to the new reality, which includes adjustments in lifestyle, relationships and the search for appropriate treatments.